Beanwatcher: uma ferramenta para o desenvolvimento de aplicações de monitoração em redes de sensores sem fio - Andre Luiz Lins de Aquino (2003)
A Wireless Network is a special type of network that uses radio waves to communicate between nodes. Recent standard approvals for WLANs, WPANs, and Broadband Wireless Access allowed users to wirelessly extend their networks in dierent scenarios such as schools, enterprises, and industries. It is estimated that 16 million people used802.11 in 2001, and this number will grow to 60 million by 2006. There are a variety of applications in wireless networks, such as military, environmental, medical and industrial applications. To develop these applications we normally use specic solutions for each case. This is a problem, making maintenance and extension a dicult task. Therefore, a tool that automatizes the eort of the programmer is of great utility.This work presents a tool based on components, called BeanWatcher. This tool allows the development of monitoring applications for wireless networks. The applications developed execute in a mobile device that acts as monitoring element of remote data and/or as an actuator. To conceive this tool, a component model was used that standardizes the monitored elements. This model makes the applications simpler andportable by generating them in dierent environments (Java, J2me and C++). As a case study, we developed applications for sensor networks. Such networks have the capacity of sensing and distributed processing. Factors related with the characteristics of the network, types and congurations of the sensors in uence the development of the applications. Through BeanWatcher we developed applications for three dierentenvironments: medical monitoring, allowing the vital data of the patients to be seen in the doctor's PDA; industrial control, where the laborer can monitor the temperature of the equipment and control it remotely; and farm monitoring that allows the agriculturist to see data about the plantation. These applications have been developed to show the viability and eciency of BeanWatcher.